The legislation on protection of juvenile from tortur end ill treatment - Романов, М. В. (Problems of legality, 2013)
The article considers legislation that regulate the protection of juvenile from torture and ill-treatment. Analyzed the basic regulations and institutions for the protection of juvenile, which are established by these acts.